Multinational enterprises and new trade theory: evidence for the convergence hypothesis - Salvador Barrios Cobos; Holger Görg; Eric Strobl (Centre for Research on Globalisation and Labour Markets, School of Economics, University of Nottingham, 2000)
According to the `convergence hypothesis' multinational companies will tend to displace national firms and trade as total market size increases and as countries converge in relative size, factor endowments, and production costs. Using a recent model developed by Markusen and Venables (1998) as a theoretical framework, we explicitly develop empirical measures to proxy bilateral FDI between two countries and address their properties with regard to the convergence hypothesis. Using a panel of data of country pairs over the years 1985-96 we econometrically test for the relationship between convergence and bilateral FDI. Our results provide some empirical support for the convergence hypothesis.
Keywords: 330; Multinationales Unternehmen; Neue Außenhandelstheorie; Theorie